2013
DOI: 10.3810/pgm.2013.03.2642
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Metastatic Colorectal Cancer Stage and Number of Treatment Courses on Patient Health Care Costs and Utilization

Abstract: Variables that had a statistically significant association with cost (P < 0.05) were sex, age group, and follow-up Charlson Comorbidity Index score after metastases. After adjusting for the number of lines of treatment received, total 4-year costs were highest among patients who presented with stage IV CRC and lowest among patients who presented with stage III CRC and developed metastatic disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 26 publications
1
13
1
Order By: Relevance
“…More specifically, a Canadian study on patients with CRC as cause of death (2006‐2010), reported 50% of deaths in SSH, a lower proportion than that observed in this study, with variations according to the zone of residence . The proportion of each place of death and the mode of management can vary according to the definition of the cases included, either people who died while being managed for cancer or people for whom cancer was the main cause of death, the study period, but also according to age, the type of cancer, its stage and its history, and comorbidities, including associated cancers, as well as the development and organization of palliative care . Observed frequencies vary according to organization of end‐of‐life care or palliative care in each country, either mainly in short‐stay hospitals, as in France, or by preferring discharge from hospital and management at home or in hospices.…”
Section: Discussioncontrasting
confidence: 57%
“…More specifically, a Canadian study on patients with CRC as cause of death (2006‐2010), reported 50% of deaths in SSH, a lower proportion than that observed in this study, with variations according to the zone of residence . The proportion of each place of death and the mode of management can vary according to the definition of the cases included, either people who died while being managed for cancer or people for whom cancer was the main cause of death, the study period, but also according to age, the type of cancer, its stage and its history, and comorbidities, including associated cancers, as well as the development and organization of palliative care . Observed frequencies vary according to organization of end‐of‐life care or palliative care in each country, either mainly in short‐stay hospitals, as in France, or by preferring discharge from hospital and management at home or in hospices.…”
Section: Discussioncontrasting
confidence: 57%
“…First, identification of lines of treatment administered was limited to the first three lines. Since, 80–90 % of mCRC patients receive a maximum of three lines of treatment [ 11 , 61 ], this limitation should not substantially reduce the applicability of our findings. Second, only drugs that require administration by a healthcare provider were considered for our analysis, and orally administered drugs (e.g., capecitabine) were not included because Medicare part D data were not available.…”
Section: Discussionmentioning
confidence: 99%
“…A claims-based algorithm, similar to those previously published 8,9 , was used to identify the first-line therapy based on the presence of claims for NCCN-recommended chemotherapy, hormonal therapy, and biologics within the first 30 days following the index date. The first-line continued until the earliest of initiation of a new agent, a gap of 90 days or more between agents (including discontinuation of all agents), or death.…”
Section: Treatment Cohortsmentioning
confidence: 99%